Upaya Guru Dalam Meningkatkan Kreativitas Anak Usia Dini Melalui Metode Bermain Peran - Amanah Rahma Ningtyas; Amrillah, HM Taufik (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to describe the efforts of teachers at RA Tunas Literasi Qur'ani Rejang Lebong in increasing the creativity of early childhood by using role-playing methods. Role playing is a form of game that teachers use by directly involving children in participating in playing a character. And creativity should be stimulated from an early age. With the hope that this creativity can become a provision for children facing the next life. This research uses a qualitative descriptive method which describes the situations that occur in the role-playing learning process carried out by teachers at RA Tunas Literasi Qur'ani Rejang Lebong. The subject of this research is the teacher at RA Tunas Literasi Qur'ani Rejang Lebong. Data collection techniques in research are observation, interviews and documentation. Based on the research results, it can be concluded that the application of the role-playing method implemented there can stimulate the creativity of early childhood. With stages 1) The teacher prepares a previously agreed theme, 2) The teacher provides the game tools that will be used, 3) The teacher divides the roles and characters to each child, 4) The teacher invites the children to act out their respective roles accompanied by encouraging interaction. with each other, 5) the teacher makes observations and then reflects with the children.